MICRO FINANCE INSTITUTION FOR HOUSING FINANCING IN INDONESIA - Merisa Kurniasari Rahardiyan Ari Wicahyo, Rika Kisnarini, Dewi Septanti, Happy Ratna Santosa (International Journal of Research Science and Management, 2017)
Microfinance institutions are one of the efforts of the government to give the right to low-income communities in the fulfillment of the need for housing. The program of special microfinance institutions for housing discussed in this study is microcredit housing. This research is a descriptive-qualitative research that compiles between microfinance institutions in Indonesia and in other developing countries in relation to housing microcredit program. It is found that from some aspects of comparability, other developing countries are better prepared in terms of micro housing microcredit program management than Indonesia